Bank Performance in Nepal: The Interplay of Bank-specific and Macroeconomic Metrics - Sharma, Abhishek (Economic Review of Nepal, 2024)
The financial performance or profitability of any entity is closely linked to both internal and external factors. This study examines the determinants of profitability in Nepalese commercial banks, focusing on a sample of five banks from 2010/11 to 2020/21. Using multiple linear regression models, the analysis found negative significant impact of and non-performing loans and liquidity on bank performance. Both ROA and ROE exhibited significant positive relationship with financial development. Although GDP had a positive impact on bank performance, the relationship is statistically insignificant. The findings suggest that internal factors, particularly asset quality and liquidity management, play a critical role in determining bank profitability. The study highlights the critical need for stringent NPL management and efficient liquidity strategies to enhance bank profitability, providing valuable guidance for policymakers, bank management, and investors in improving financial stability and performance.